The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1002/(sici)1097-0185(199712)249:4<435::aid-ar2>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Weber's salivary glands of the root of the tongue in the rat

Abstract: The mucus elaborated by Weber's glands undoubtedly aids in swallowing dry food. We postulate that the serous cells in these glands, as in the more anterior von Ebner's glands, might play a role in the mechanism of taste, especially where posteriorly situated, nonlingual taste buds are concerned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 24 publications
(29 reference statements)
8
31
0
Order By: Relevance
“…The presence of serous and mucous glands in the lingual radix of the degu, as well as mixed glands in this area of the rat's tongue is undoubtedly related to the taste perception and swallowing of dry food, respectively. This was also suggested by Nagato et al (1997).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The presence of serous and mucous glands in the lingual radix of the degu, as well as mixed glands in this area of the rat's tongue is undoubtedly related to the taste perception and swallowing of dry food, respectively. This was also suggested by Nagato et al (1997).…”
Section: Discussionsupporting
confidence: 73%
“…The lingual glands ducts were observed on the dorsal and lateral surfaces of the root in the Patagonian cavy (Emura et al 2011). Nagato et al (1997) focused on the Weber's salivary glands of the root of the tongue in the rat. These glands were tubulo-acinar (mixed), consisting of mucous tubules with serous demilunes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultrastructure of rat Weber's glands has been described exquisitely by Nagato et al (1997). In addition to the features described above, it was observed that the serous demilunes have direct access to the lumina of the mucous acini that they cap and no secretory canaliculi were seen.…”
Section: Lingual Glands Of Weber (Weber's Glands)mentioning
confidence: 91%
“…Nagato et al (1997) attributed the foci of fused secretory granules in some mucous cells in Weber's glands to this phenomenon. This would be consistent with the suggestion by Eldar and Elowsitz (2010) that differences in responses among cells performing the same function, some quick and others slow to react to stimuli, allows for sustained levels of performance during long periods of activity.…”
Section: Posterior Buccal Glandsmentioning
confidence: 99%